(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today’s generation, academic performance is very important, especially for working students who work just to continue their studies because good academics are a big help for students who are more likely to have better employment benefits, higher incomes, and greater levels of self-confidence and self-esteem. Students struggle to balance working, studying, and family obligations without having a negative impact on their academic performance. This research aims to encourage working students to pursue and complete a college degree to be competitive in the future. The study utilized a descriptive research method, which was distributed to a hundred (100) working students, 25 representatives from each of all levels, from the 1st to the 4th year in the Bestlink College of the Philippines Novaliches, Quezon City. The researchers used simple sampling techniques in disseminating questionnaires to the respondents. This study is limited only to students who are currently enrolled and who are also working at Bestlink College of the Philippines Novaliches, Quezon City. Only those BSHM working students are allowed to participate in the research. There should be a consideration when it comes to the age of the students who want to work; there are students who want to work, but some of them are not qualified because of age qualification. The school must have at least a job fair inside the campus for those who want to work while studying, and, in that way, they can help the students get jobs. Apply to the scholarships offered by the government and other organizations that are willing to help those who are deserving of their support.